PENINGKATAN KUALITAS BIBIT NYAMPLUNG (Calophyllum inophyllum L) DAN MALAPARI (Pongamia pinnata L) DENGAN APLIKASI MIKORIZA DAN Trichoderma spp. - Benyamin Dendang; Aditya Hani; Encep Rachman (Jurnal Pemuliaan Tanaman Hutan, 2018)
Nyamplung and Malapari a potential bioenergy crops on marginal land to be developed on the coastal land. The constraints of the coastal land is the less of water and soil nutrient. Input technology is needed in order to suceed the crop planting such as using bio fertilizer. Mycorrhizae plays an essential role in helping plants to absorb phosphate and increase the resistance to drought. Trichoderma spp involves in producing beneficial hormones for metabolism and helps break down organic matter. Utilization of biofertilizer is still rarely used as treatment in bioenergy plant seedlings. This study aimed to determine the quality of nyamplung and malapari seedlings after mycorrhizal and Trichoderma spp application in the nursery. Experiments were arranged in a complete randomized block design (RCBD). The treatment of media: soil as control (T), soil+organic fertilizer with ratio of 3:1(TK), soil+organic fertilizer+mycorhizae 10 g (TKM), soil+organic fertilizer+Trichoderma spp 10 g (TKT), soil+organic fertilizer+mycorrhizal 10 g+Trichoderma 10 g (TC). Application was done when the seedlings reached 1 (one) month old. Biofertilizer was sown around seedling roots. Each treatment consisted of 50 samples and 3 replications so the total seedlings were 750 seedlings. The results showed that after 6 and 12 months treatment malapari with organic fertilizer + mikoriza + Tricoderma spp (TC) gained 67.5% taller and 427% larger on dry weight of leaf than the control, whereas in nyamplung seedlings, TC treatment resulted better growth with diameter 8% larger, root length 78.56% longer, and total dry weight 7.88% heavier compared to control (T).